Estudio de factibilidad para la creación de una empresa dedicada a la recreación infantil a través de atracciones electromecánicas en el municipio de Calarcá Quindío (2015)
The development of this research is conducted through a feasibility study , which is planning the creation of a company dedicated to promoting electromechanical games with excellent quality attractions for children and adolescents in the city of Calarca At the inner of chapter one was made the planning, the formuling and the systemming of the problem. To collect the information (primary source) was used as tecnitian instrument the survey that was applied to 378 adults, parents and representatives of boys, girls and teenagers residents in the city of Calarcá Quindio. In the chapter 2, general aspects of the social economic environment of the country and Quindio Department. In chapter 3, a market study took place, through it was identified the offered service product, analysis, historical behaviour and projection of the offered demanding on this locality. On the same way was analyzed the offert, deciding the the principal competitors on local and departmental levels, same as determination and projection of prices for the offered services by the company Within the chapter 5, the technical study, through it, the size and capacity is detected. The localization and engineering of the project, , description of the primary resources and needed items for the creation of the company was made. The content of chapter 5 is related to the study of the company, legal and enviromental aspects, designing manuals and functions among others. on chapter 6, the financial study where It was performed an evaluation of costs, capital and investments was determined the present net price, inner return rates, important aspects of the creation of DIVERFAMILY company. Trough them was determined the economic and financial rentability. In chapter seven, recommendations and conclusions are presented.